First application of dynamic oxygen-17 magnetic resonance imaging at 7 Tesla in a patient with early subacute stroke - Ebersberger, Louise; Kratzer, Fabian; Potreck, Arne; Niesporek, Sebastian; Keymling, Myriam; Nagel, Armin Michael; Bendszus, Martin; Wick, Wolfgang; Ladd, Mark E.; Schlemmer, Heinz-Peter; Hoffmann, Angelika; Platt, Tanja; et al. (Frontiers in neuroscience, 2023)
Dynamic oxygen-17 (17O) magnetic resonance imaging (MRI) is an imaging method that enables a direct and non-invasive assessment of cerebral oxygen metabolism and thus potentially the distinction between viable and non-viable tissue employing a three-phase inhalation experiment. The purpose of this investigation was the first application of dynamic 17O MRI at 7 Tesla (T) in a patient with stroke. In this proof-of-concept experiment, dynamic 17O MRI was applied during 17O inhalation in a patient with early subacute stroke. The analysis of the relative 17O water (H217O) signal for the affected stroke region compared to the healthy contralateral side revealed no significant difference. However, the technical feasibility of 17O MRI has been demonstrated paving the way for future investigations in neurovascular diseases.
Gesehen am 25.09.2023